Frustration and luxury brands: silencing anpoliteness in consumer relations on the online platform Reclame Aqui (ModaPalavra e-periódico, 2024)
Consumption practices are social, cultural, economic, symbolic, relational and affectionate, and have frustration as a possibility. The digital platform Reclame Aqui brings together conflicting ways of saying in buying and selling relationships and indicates that consumers of luxury brands seem to avoid exposing their dissatisfaction. The reduced enunciative materialization of complaints related to the Hermès, Zegna and Armani brands indicates eventual consumer satisfaction with the products, the service, the solution of problems arising from consumer experiences or a probable inconvenience in registering complaints online. The silencing of consumers was evaluated under the concept of discourse analysis of the French school, in addition to three registered publications. It is concluded that the few complaints are discursively constructed with elements of politeness, in an attempt to preserve faces and maintain consumer relations in a context in which disappointment prevents the subject from satisfactorily experiencing the hedonism promised by the consumer society.
Keywords: consumption; luxury brands; frustration